2021
DOI: 10.1111/febs.15698
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ALDH1A1 by omeprazole reduces cell oxidative stress damage

Abstract: Under physiological conditions, cells produce low basal levels of reactive oxygen species (ROS); however, in pathologic conditions ROS production increases dramatically, generating high concentrations of toxic unsaturated aldehydes. Aldehyde dehydrogenases (ALDHs) are responsible for detoxification of these aldehydes protecting the cell. Due to the physiological relevance of these enzymes, it is important to design strategies to modulate their activity. It was previously reported that omeprazole activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…However, whether activation or inhibition of ALDH enzymes exerts beneficial effects depends on the specific conditions, necessitating a greater understanding of the role-played by ALDH1A1 in specific diseases. [43][44][45][46] Solute carrier family-25 (SLC25) is a superfamily of transporters in the mitochondrial inner membrane in mammals, and SLC25 member-30 (SLC25A30) has been implicated in the regulation of ROS. 47 The Slc25a30 gene encodes kidney mitochondrial carrier protein-1 (KMCP1), which transports sulfate and thiosulfate across the inner mitochondrial membrane and thereby modulates the level of the important gaseous signaling molecule, hydrogen sulfide (H 2 S).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether activation or inhibition of ALDH enzymes exerts beneficial effects depends on the specific conditions, necessitating a greater understanding of the role-played by ALDH1A1 in specific diseases. [43][44][45][46] Solute carrier family-25 (SLC25) is a superfamily of transporters in the mitochondrial inner membrane in mammals, and SLC25 member-30 (SLC25A30) has been implicated in the regulation of ROS. 47 The Slc25a30 gene encodes kidney mitochondrial carrier protein-1 (KMCP1), which transports sulfate and thiosulfate across the inner mitochondrial membrane and thereby modulates the level of the important gaseous signaling molecule, hydrogen sulfide (H 2 S).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether activation or inhibition of ALDH enzymes exerts beneficial effects depends on the specific conditions, necessitating a greater understanding of the role-played by ALDH1A1 in specific diseases. 4346…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that both alcohol and endogenous aldehydes damage chromosomes and increase the mutation rate of stem cells ( Garaycoechea et al, 2018 ). The activation of Aldh1a1 was found with the ability to reduce cell oxidative stress damage ( Calleja et al, 2021 ). We found that beaver cells exhibited better tolerance to ethanol than mouse cells and showed strikingly enhanced capabilities for metabolizing MDA and HNE ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, researchers have found that ALDH1A1 had vital physiological and pathophysiological functions in many systems, such as the central nervous system, as well as inflammatory and metabolic disorders (5)(6)(7). ALDH1A1 overexpression has been found to play an important role in obesity, diabetes, and other diseases (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%